2015
DOI: 10.1136/bcr-2014-208657
|View full text |Cite
|
Sign up to set email alerts
|

Phaeochromocytoma with hypercortisolism and hypercalcaemia

Abstract: SUMMARYWe report a case of phaeochromocytoma associated with hypercortisolism and hypercalcaemia in a 62-year-old man. The patient presented to clinic, with a 3-year history of exertional headaches, and a 4-month history of increasing fatigue, sweating and palpitations, loss of appetite and weight, and sleepiness. He did not have a medical, family or social history that could account for these symptoms. 24 h urinary catecholamines, plasma metanephrines, 24 h urinary cortisol and adjusted serum calcium, were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It has been suggested that there may be an interaction between the adrenal medulla and cortex. Although coexistent cases of pheochromocytoma and cortisol-secreting adrenocortical adenoma have been previously reported 22 24 , it is quite rare. Even rarer, an adrenal corticomedullary mixed tumor has been shown, including in our group 19 .…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that there may be an interaction between the adrenal medulla and cortex. Although coexistent cases of pheochromocytoma and cortisol-secreting adrenocortical adenoma have been previously reported 22 24 , it is quite rare. Even rarer, an adrenal corticomedullary mixed tumor has been shown, including in our group 19 .…”
Section: Discussionmentioning
confidence: 98%
“…As there are numerous effects resulting from aand b-receptor stimulation, PPGL can less commonly present with symptoms including hypercalcaemia and hypercortisolaemia 28 due to the increased secretion of ACTH and thromboembolic events. 29,30 Phaeochromocytoma crisis PPGL crisis is defined as an acute severe presentation of a catecholamine-induced haemodynamic instability causing end-organ damage or dysfunction.…”
Section: Unusual Symptomsmentioning
confidence: 99%